Influence of parental attitudes towards basic education students academic achievements and motivation in basic science in Anambra state - Christian-Ike, Nwanneka Oluchukwu; Chukwuemenam, Joel Patrick; Nnalue, Henrietta Obioma; Ibeh, Joseph (Univeritas Papua, 2025)
A research on the influence of parental attitude towards students' motivation and academic achievement in Awka South Local Government Area, Anambra State. Four research questions guided the study. The study adopted a descriptive research survey design. The population used was 2,604 students from Upper Basic 8. The sample size used is 160 basic science students. The method of reliability is Cronbach's alpha. The instrument used was a structured questionnaire, which yielded a reliability coefficient of 0.91. The method of analysis used was the arithmetic mean. The study found that parental attitudes, such as encouraging children to excel academically, attending school events, providing support during academic struggles, discussing the importance of education, praising and reinforcing good academic performance, supplying educational materials, ensuring regular school attendance, dismissing their efforts in school, showing a lack of interest in children's academic performance, blaming them for poor results without offering help, and negatively comparing their performance with other students, significantly influence students' academic achievement and motivation. The study's findings recommend that schools and educational authorities should implement regular workshops and seminars to educate parents on the importance of their attitudes and involvement in their children's academic journey. Educational policymakers should formulate policies that encourage or require schools to develop programmes for increased parental involvement.